CRUSTAL STRUCTURE DEDUCED FROM RECEIVER FUNCTIONS VIA SINGLE-SCATTERING MIGRATION - Bertrand E.; Deschamps A.; Virieux J. (My University, 2002)
An investigation of the teleseismic P-wave coda is performed using the single-scattering approximation. The method allows one to image short-wavelength scale (<=2 km) velocity and density heterogeneities and structures that are barely detected by traveltime tomography. Source effects are removed by using receiver functions for data interpretation, but the amplitude (especially the sign of the signal) is synthesized. Both broad-band seismological stations in the southwestern Alps (France) and Campanian plain (Italy) are used for the illustration of the proposed method. Because of the large aperture of our arrays, laterally small-scale heterogeneities are difficult to image and we must assume lateral continuity of the detectable structure. If so, we show that this depth migration based on a single-scattering approach can recover both the depth and the geometry of the main discontinuities below the studied areas. In the southwestern Alps, we underline a complex crustal structure and Moho dipping topograph
Keywords: body waves; broad-band; crustal structure; Moho discontinuity; P-to-S conversions; scattering; waveform analysis